Pengenalan Budaya Komunikasi Bisnis Jepang Melalui Kurasu Katsudo - Maharani Patria Ratna (KIRYOKU, 2019)
Introduction of Japanese business communication culture to Japanese learners is one of the important elements in learning Japanese. This introduction can be done through kurasu katsudo 'class activities' to make it easier for students to understand. Kurasu Katsudo is strongly suggested done in various ways and repeatedly by inserting information about cultural elements in the middle of the teaching process. The purpose of this study is to describe Japanese business communication culture through kurasu katsudo. This research is a qualitative descriptive study. Data are collected by library method through several Japanese textbooks. The results of this study indicates that group orientation as one of the Japanese business communication culture can be introduced through the learning of jikoshokai 'self-introduction' and meishi kokan 'exchange business cards'. In addition, hierarchical culture can be taught by the teaching of osewa ni narimashita expression and juju hyogen expression. While the horenso culture can be introduced through learning the N gurai Vru monda sentence pattern.